Mesoscale eddy variability in the southern extension of the East Madagascar Current: Seasonal cycle, energy conversion terms, and eddy mean properties. Issue 10 (30th October 2014) - Halo, Issufo; Penven, Pierrick; Backeberg, Björn; Ansorge, Isabelle; Shillington, Frank; Roman, Raymond
Abstract In this study, we used more than 17 years of satellite altimetry observations and output from an ocean model to investigate the mesoscale eddy variability and forcing mechanisms to the south of Madagascar. Analysis of energy conversion terms in the model has shown seasonality on eddy formation, both by barotropic and baroclinic instabilities: maximum in winter (JJA) and minimum in summer (DJF). The eddies were mainly formed in the upper ocean (0–300 m) and at intermediate depths (800–2000 m) by barotropic and baroclinic instabilities, respectively. The former dominated in the southeastern margin of Madagascar, and the latter to the southwest, where the South‐East Madagascar Current (SEMC) separates from the continental shelf. Seasonality of the eddy formation appeared linked with the seasonal intensification of the SEMC. The energy conversion terms indicated that the eddies have a significant contribution to the large‐scale circulation, but not being persistent throughout the year, occurring mainly during the fall season (MAM). Eddy demography from altimetry and model provided information on eddy preferential sites for birth, annual occurrence (6–13 per year), eddy mean diameter (124–178 km), mean amplitude (9–28 cm), life‐time (90–183 days), and maximum traveling distances (325–1052 km). Eddies formed to the southwest of Madagascar exhibited distinct characteristics from those formed in the southeast. Nevertheless, all eddies were highly nonlinear, suggesting that they are potential vectors of connectivity between Madagascar and Africa. This may have a significant impact on the ecology of this region.